(untitled) (Fiep Bulletin - online, 2014)
This article tries to reflect about the Physical education teacher formation from the presuppositions which in every teaching practice there is an explicit or implicit social engagement; and that this engagement comes from some moment of the teacher human formation, that the initial formation is fundamental or even decisive in this teacher compromising.